1-(1-Decyl-2-oxoindolin-3-ylidene)thiosemicarbazide - Mamari, K.; Zerzouf, A.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title 1-alkylisatin 3-thiosemicarbazone, C(19)H(28)N(4)OS, the imine C=N bond has a Z configuration, whereas the N-N-C=S unit has an E conformation. In the crystal, molecules are connected by N-H center dot center dot center dot O hydrogen bonds, forming zigzag chains running along the b axis.